Implementasi Fatwa Nomor 25/DSN-MUI/III/2002 Dalam Akad Gadai Emas - Hanggara, Dimas Tomy; Jalaludin, Akhmad; Ainul Yaqin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The purpose of this study was to determine the practice of pawning gold, the implementation of the DSN MUI fatwa no. 25/DSN-MUI/III/2002 regarding Rahn and the reasons why the DSN MUI fatwa no. 25/DSN-MUI/III/2002 was not fully implemented. At PT. Pekalongan Sharia Pawn Services. This type of research is a field research (field-research) with the object of research is the implementation of the fatwa DSN MUI number 25/DSN-MUI/III/2002 in the gold pawn contract at PT. Sharia Pawn Services. Sources of data in the form of primary and secondary data, primary data obtained by observation and interview techniques while secondary data obtained by documentation that is utilizing sources of books, journal articles, websites or websites. And the data analysis used descriptive qualitative which was concluded by means of inductive thinking. The conclusion of this study is that the implementation of the DSN MUI fatwa no. 25/DSN-MUI/III/2002 regarding rahn.at PT. The Sharia Pawn Service has been in accordance with its practice, although in the sales process it is not in accordance with the provisions of the MUI DSN fatwa, but the purpose of the sale of collateral goods that are not redeemed in accordance with the MUI DSN fatwa is to pay off debtors' debts and pay their ujrah.